Peningkatan Keterampilan Menyusun Teks Cerita Sejarah melalui Media Youtube - Aziz Mansur (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
This research is motivated by the low skills of students in writing historical story text facts in class XII MIPA 3 MAN 1 Ciamis. This study aims to improve the skills of compiling historical story texts through youtube media in class XII MIPA 3 MAN 1 Ciamis. The research method uses Classroom Action Research. The research subjects were 23 students. Data collection techniques were carried out by tests, observations, interviews and discussions. Data collection tools include tests, observations, interviews, and questionnaires. The results showed the teacher's ability to use learning media in the first cycle obtained a score of 39 or 79%, the second cycle increased to 45 or 86.53%, and in the third cycle it became 50 or 96.15% of the ideal score of 52. Student skills in compiling historical story texts on learning activities in the first cycle obtained an average value of 15.5 or 77.5%, the second cycle 16.75 or 83.75%, and in the third cycle 18.75 or 93.75% of the ideal score was obtained. 20 or 100%. The average score of the students' initial test results was 79.09. After using youtube media in the first cycle the average score rose to 81.74, in the second cycle the average score increased to 83.78, in the third cycle the average score was 89.30. Based on those results, the use of youtube media can improve the skills of compiling historical story texts.